Scar assessment as a measure of outcome in cleft lip repair (2011)
As opposed to healing of wounds that occur in early intrauterine life which heals rapidly and without scarring, postnatal cutaneous wound healing is a complex and dynamic process and the end result is formation of a scar. Although the degree of scarring following any surgery depends on many factors, the likelihood of forming more profound howbeit hypertrophic scar may be more in the dark African skin. This has been noted to be a reason for reduced enthusiasm on the part of some adult Africans from embracing cosmetic surgical procedures. Varying degrees of scarring occur following the repair of clefts in children and the degree of scarring may affect the cosmetic and functional outcome of these repairs. With the advent of SmileTrain intervention in the management of clefts in Nigeria, there has been a great increase in the number of surgeries carried out for cleft lip repair such that the resultant scar from these surgeries needs to be assessed and controlled in order to improve the outcome of the surgical interventions. The aim of this paper therefore is to highlight the different methods by which these scars can be assessed and the assessment incorporated into the outcome measures of cleft lip repair. Method: A literature search on scar assessment using the PubMed was conducted. The articles that were written in English Language were retrieved and reviewed with particular attention to those that focus more on the assessment of linear scars. Parameters employed in each of the assessment tools were noted and the suitability of such tool for our patient population was evaluated. Some of the assessment tools were applied to patients that had cleft lip repair in our centre to determine if they are appropriate for use in our patients and possible modifications for their use were suggested. Result: Several scar assessment tools were indentified. The following were found to be applicable to cleft lip assessment specifically - Visual Analogue Scale, Vancouver Scar Scale (VSS), Patient and Observer Scar Assessment Scale (POSAS), Wound Evaluation Scale (WES), Manchester Scar Scale (MSS), Stony Brook Scar Evaluation Scale (SBSES). Application of the methods to our patient population reveals that there is need for some form of modification as discussed below in order to achieve best results. Discussion: Patients who come for cleft lip repair present mainly because of the quest of them patients or their parents for improvement in their appearance. On the part of the surgeon however, the repair is necessary in order to restore form (cosmesis) and function. The degree of scarring after surgery has a role to play in outcome because it can affect both form and function. Assessment of post operative scars prompt the surgeon to take measures that will lead to an improvement of outcome in the subsequent patient he operates and the tools used for this assessment should be adequate to provide insight into what needs to be done to ensure improvement.